Frequency of low back pain among nurses working in Jinnah hospital Lahore - Rasheed, Hammad; Rashid, Junaid; Javeed, Rana Saqib (International Journal of Endorsing Health Science Research, 2017)
Background: Nursing is a healthcare profession that is concerned with maintaining and promoting the health of the patients. Because of their work environment and workload nurse are at the very high risk of many occupational health problems. Among all these; musculoskeletal problems are most common especially the low back pain. Methods: A descriptive cross-sectional study design was used. A sample size of 92 nurses was calculated and questionnaires were distributed among them and information was collected on socio-demographic characteristics, job history, frequency, severity and pattern of low back pain. Data was analyzed using the Statistical Package for the Social Sciences (SPSS) version 23 for windows and Microsoft Excel 2013. Descriptive statistics i.e., percentage, mean were used to interpret the data. Chi-square and P-value were used to find associations between dependent and independent variables. Results: The frequency of low back pain among nurses was 65.1%. 12 months frequency was 57.8% and 7 days frequency was 32.5% with majority of nurses describing pain of Moderate intensity. The frequency of low back pain was high in nurses more than 30 years old, married, overweight/obese and those with more than 15 years of work experience. Conclusions: About 65% of nurses working in Jinnah Hospital Lahore were suffering from low back pain which indicates high prevalence and is in line with prevalence of low back pain in the developed countries. Therefore, it is recommended to maintain the Body Mass Index in the normal ranges and also maintain proper body mechanics and posture and use assistive devices in lifting the patients.